Low sex hormone-binding globulin is associated with hypertension: a cross-sectional study in a Swedish population - Daka, Bledar (BioMed Central, 2013)
BACKGROUND: The aim of this study was to investigate the association of sex hormone-binding globulin (SHBG) and hypertension in a Swedish population. METHODS: The study is based on a random sample of a Swedish population of men and women aged 30–74 years (n=2,816). Total testosterone, oestradiol and SHBG were measured in 2,782 participants. Free androgen index was then calculated according to the formula FAI=100 × (Total testosterone)/SHBG. Hypertension was diagnosed according to JNC7. RESULTS: In men, but not in women, significant association between SHBG and both diastolic (diastolic blood pressure: β=−0.143 p<0.001) and systolic blood pressure (systolic blood pressure β=−0.114 p<0.001) was found. The association was still significant after adjusting for age, body mass index (BMI), homeostatic model assessment insulin resistance (HOMA-IR), triglycerides, high density lipoproteins (HDL) and C-reactive protein (CRP) (diastolic blood pressure: β=−0.113 p<0.001; systolic blood pressure β=−0.093 p=0.001). An inverse association was observed between SHBG and hypertension in both men (B=−0.024 p<0.001) and women (B=−0.022 p<0.001). The association was still significant in women older than 50 years after adjustments for age, BMI, physical activity, CRP and alcohol consumption (B=−0.014, p=0.008). CONCLUSION: In conclusion, these results show a strong association between SHBG and blood pressure independent of major determinants of high blood pressure. This association might be addressed to direct effects of SHBG in endothelial cells through the receptor for SHBG. If this is confirmed by other observational and experimental studies, it might become a new field for the development of therapies for lowering blood pressure.